The road to resilience: Rethinking responses to food crises - Kosec, Katrina; Swinnen, Johan (International Food Policy Research Institute, 2023)
In 2022, the world faced multiple crises. Globally, disruptions to food systems continued amid a protracted pandemic, major natural disasters, civil unrest and political instability, and the growing impacts of climate change, all while the war in Ukraine exacerbated a global food and fertilizer crisis. Yet some aspects of food systems have proved surprisingly resilient in the face of crisis. The International Food Policy Research Institute’s (IFPRI’s) 2021 Global Food Policy Report: Transforming Food Systems after COVID-19 showed, for example, that adopting new business models helped to keep food value chains functioning during the pandemic, and expanding social protection programs reduced negative impacts on food security.